Culturally Responsive Teaching in an Undergraduate Online General Education Course - Barbara Schirmer; Alison Lockman (Online Learning, 2022)
While inclusive pedagogies such as culturally responsive teaching may be common in face-to-face learning, there is little published research regarding culturally responsive teaching and learning in higher education online settings. It is not known whether faculty members employ culturally responsive teaching strategies or what types of strategies they use in online courses. The purpose of this study was to determine whether online faculty members practice culturally responsive teaching and to explore the characteristics of culturally responsive teaching that are reflected in the responses of 12 instructors in a fully online undergraduate general education course required in the first few terms of enrollment. Qualitative methodology was utilized, involving deductive and inductive coding methods of analysis. Data were coded deductively based on four major categories of cultural competence: sociopolitical/cultural consciousness, community of learners, and high academic expectations. Data were coded inductively for culturally nonresponsive interactions. Findings from deductive analysis revealed partial use of culturally responsive teaching strategies in online classrooms. Results for inductive analysis showed themes of nondifferentiated responses, missed opportunities for addressing linguistic or cultural differences, and lack of encouragement for collaboration or sense of community. These findings indicate a need for further research in culturally responsive teaching in online learning as well as faculty professional development that focuses on culturally responsive teaching.